Prediction Tools in Spine Surgery: A Narrative Review - Martin Coia Jadresic; Joseph F Baker (Spine Surgery and Related Research)
There have been increasing reports on prediction models in spine surgery. Interest in prognostic tools or risk calculators can facilitate shared decision-making about treatment between patients and clinicians. In recent years, there has been a steady increase in the number of models developed using varying methods. External validation is an essential component of prediction model testing to ensure the appropriate use of these models in populations outside of the developing center. This narrative review aimed to provide an overview of the literature describing the development and validation of prediction models in the field of spine surgery.